Red light perovskite quantum dot borosilicate glass material as well as preparation method and application thereof
By introducing AgI into red light perovskite quantum dot borosilicate glass and using autologous crystallization method, the problem of low fluorescence quantum yield of red light perovskite quantum dot glass is solved, and high fluorescence quantum yield and Stability, suitable for display, lighting and optical communication.
Patent Information
- Application Number
- CN202411369805.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The fluorescent quantum yield of existing red light perovskite quantum dot glasses is generally low, and it is urgent to design red light perovskite quantum dot glasses with high fluorescence quantum yield.
By introducing AgI into the red light perovskite quantum dot borosilicate glass material and using autologous crystallization method to prepare CsPbBrI2 perovskite quantum dots in borate glass, avoiding further annealing and heat treatment, simplifying the process and reducing energy Consumption.
Significantly improves the photoluminescence fluorescent quantum yield of red light perovskite quantum dot borosilicate glass, enhances its water oxygen stability and thermal stability, is suitable for display, lighting and optical communication, and has a simple process and low cost. , suitable for industrial production.
Smart Images

Figure CN119241080A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid luminescent materials, and in particular to a red light perovskite quantum dot borosilicate glass material and a preparation method and application thereof. Background Art
[0002] With the rapid development of optoelectronic technology, red luminescent materials have broad application prospects in display, lighting, optical communication and other fields. Among them, perovskite quantum dot materials have attracted widespread attention due to their excellent optoelectronic properties (such as high optical absorption coefficient, narrow emission spectrum line width, high fluorescence quantum yield and adjustable spectral range). Although encapsulating perovskite quantum dots in glass can improve the stability of perovskite quantum dots, it will also reduce its fluorescence quantum yield, resulting in the current red light perovskite quantum dot glass generally having a low fluorescence quantum yield. It is urgent to design a red light perovskite quantum dot glass with high fluorescence quantum yield. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a red light perovskite quantum dot borosilicate glass material and a preparation method and application thereof. The red light perovskite quantum dot borosilicate glass material provided by the present invention has a high photoluminescence fluorescence quantum yield of the perovskite quantum dots.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The invention provides a red light perovskite quantum dot borosilicate glass material. The chemical composition of the material comprises, by amount of substance, 56-68 parts of H3BO3, 28-34 parts of SiO2, 5-9 parts of ZnO, 13-17 parts of Na2CO3, 1-5 parts of Cs2CO3, 1-4 parts of PbBr2, 3-7 parts of PbI2, 1-2 parts of NaBr, 1-4 parts of NaI and 0-0.6 parts of AgI, and the amount of AgI used is not 0.
[0006] Preferably, the chemical composition of the red light perovskite quantum dot borosilicate glass material includes, by amount of substance, 56 to 68 parts of H3BO3, 28 to 34 parts of SiO2, 5 to 9 parts of ZnO, 13 to 17 parts of Na2CO3, 3 parts of Cs2CO3, 2 parts of PbBr2, 5 parts of PbI2, 1 part of NaBr, 3 parts of NaI and 0 to 0.6 parts of AgI.
[0007] The present invention provides a method for preparing the red light perovskite quantum dot borosilicate glass material described in the above technical solution, comprising the following steps:
[0008] According to the chemical composition of the red light perovskite quantum dot borosilicate glass material, the prepared raw materials are mixed and then melted to obtain a glass melt;
[0009] The glass melt is cast and then cooled to obtain the red light perovskite quantum dot borosilicate glass material;
[0010] Preferably, the melting temperature is 1100-1250° C. and the melting time is 10-20 min.
[0011] Preferably, the mixing includes grinding and mixing; the particle size of the mixture obtained by grinding and mixing is 2 μm.
[0012] Preferably, the casting time is less than 6 minutes.
[0013] Preferably, the casting molding comprises: pouring the glass melt onto a preheated plate and letting it stand.
[0014] Preferably, the temperature of the preheated preheating plate is 400°C.
[0015] Preferably, the pouring time is less than 1 min.
[0016] The present invention provides the application of the red light perovskite quantum dot borosilicate glass material described in the above technical scheme or the red light perovskite quantum dot borosilicate glass material prepared by the preparation method described in the above technical scheme in display, lighting or optical communication.
[0017] The present invention provides a red light perovskite quantum dot borosilicate glass material, which, in terms of the amount of substances, has a chemical composition comprising: 56-68 parts of H3BO3, 28-34 parts of SiO2, 5-9 parts of ZnO, 13-17 parts of Na2CO3, 1-5 parts of Cs2CO3, 1-4 parts of PbBr2, 3-7 parts of PbI2, 1-2 parts of NaBr, 1-4 parts of NaI and 0-0.6 parts of AgI, and the amount of AgI is not 0. The present invention improves the photoluminescence fluorescence quantum yield of the red light perovskite quantum dot borosilicate glass material by introducing AgI into the red light perovskite quantum dot borosilicate glass material; moreover, the present invention improves the water-oxygen stability and thermal stability of the red light-emitting CsPbBrI2 perovskite quantum dots by embedding the perovskite quantum dots into the borosilicate glass, has good environmental stability, and can effectively exert the optical properties of the perovskite quantum dots.
[0018] The method for preparing red light perovskite quantum dot borosilicate glass material described in the above technical solution provided by the present invention successfully prepares red light-emitting CsPbBrI2 perovskite quantum dots in borosilicate glass by a self-crystallization method. The preparation process does not require further annealing and heat treatment, is simple to operate, has low cost, low energy consumption, low environmental pollution, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1XRD diffraction patterns of red light perovskite quantum dot borosilicate glass materials prepared in Examples 1 to 4 and Comparative Example 1;
[0020] Figure 2 The emission spectra of the red light perovskite quantum dot borosilicate glass materials prepared in Examples 1 to 4 and Comparative Example 1;
[0021] Figure 3 PLQY diagram of the red light perovskite quantum dot borosilicate glass material prepared in Comparative Example 1;
[0022] Figure 4 This is a PLQY diagram of the red light perovskite quantum dot borosilicate glass material prepared in Example 3;
[0023] Figure 5 The lifetime decay curve diagram of the red light perovskite quantum dot borosilicate glass material prepared in Examples 1 to 4 and Comparative Example 1;
[0024] Figure 6 This is a graph showing the change in photoluminescence intensity of the red light perovskite quantum dot borosilicate glass material prepared in Example 3 after being immersed in water for 90 days;
[0025] Figure 7 This is a graph showing the photoluminescence intensity variation of the red light perovskite quantum dot borosilicate glass material prepared in Example 3 under continuous irradiation with 6W ultraviolet light for 90 days;
[0026] Figure 8 This is a graph showing the change in photoluminescence intensity of the red light perovskite quantum dot borosilicate glass material prepared in Example 3 after five cycles at 300K and 400K. DETAILED DESCRIPTION
[0027] The invention provides a red light perovskite quantum dot borosilicate glass material. The chemical composition of the material comprises, by amount of substance, 56-68 parts of H3BO3, 28-34 parts of SiO2, 5-9 parts of ZnO, 13-17 parts of Na2CO3, 1-5 parts of Cs2CO3, 1-4 parts of PbBr2, 3-7 parts of PbI2, 1-2 parts of NaBr, 1-4 parts of NaI and 0-0.6 parts of AgI, and the amount of AgI used is not 0.
[0028] Calculated by the amount of substance, the chemical composition of the red light perovskite quantum dot borosilicate glass material provided by the present invention includes 56 to 68 parts of H3BO3. In a specific embodiment, the amount of H3BO3 can be 56, 60, 62, 64, 66 or 68 parts.
[0029] Based on the molar fraction of the H3BO3, the chemical composition of the red light perovskite quantum dot borosilicate glass material provided by the present invention includes 28 to 34 parts of SiO2. In a specific embodiment, the molar fraction of the SiO2 can be 28, 29, 30, 31, 32, 33 or 34 parts.
[0030] Based on the molar fraction of the H3BO3, the chemical composition of the red light perovskite quantum dot borosilicate glass material provided by the present invention includes 5 to 9 parts of ZnO. In a specific embodiment, the molar fraction of the ZnO can be 5 parts, 6 parts, 7 parts, 8 parts or 9 parts.
[0031] Based on the molar fraction of the H3BO3, the chemical composition of the red light perovskite quantum dot borosilicate glass material provided by the present invention includes 13 to 17 parts of Na2CO3. In a specific embodiment, the molar fraction of the Na2CO3 can be 13 parts, 14 parts, 15 parts, 16 parts or 17 parts.
[0032] Based on the molar fraction of the H3BO3, the chemical composition of the red light perovskite quantum dot borosilicate glass material provided by the present invention includes 1 to 5 parts of Cs2CO3. In a specific embodiment, the molar fraction of the Cs2CO3 can be 1 part, 2 parts, 3 parts, 4 parts or 5 parts.
[0033] Based on the molar fraction of the H3BO3, the chemical composition of the red light perovskite quantum dot borosilicate glass material provided by the present invention includes 1 to 4 parts of PbBr2. In a specific embodiment, the molar fraction of the PbBr2 can be 1 part, 2 parts, 3 parts or 4 parts.
[0034] Based on the molar fraction of the H3BO3, the chemical composition of the red light perovskite quantum dot borosilicate glass material provided by the present invention includes 2 to 7 parts of PbI2. In a specific embodiment, the molar fraction of the PbI2 can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts or 7 parts.
[0035] Based on the molar fraction of the H3BO3, the chemical composition of the red light perovskite quantum dot borosilicate glass material provided by the present invention includes 1 to 2 parts of NaBr. In a specific embodiment, the molar fraction of the NaBr can be 1 part or 2 parts.
[0036] Based on the molar fraction of the H3BO3, the chemical composition of the red light perovskite quantum dot borosilicate glass material provided by the present invention includes 1 to 4 parts of NaI. In a specific embodiment, the molar fraction of the NaI can be 1 part, 2 parts, 3 parts or 4 parts.
[0037] Based on the molar fraction of the H3BO3, the chemical composition of the red light perovskite quantum dot borosilicate glass material provided by the present invention includes 0 to 0.6 parts of AgI, and the amount of AgI is not 0. In a specific embodiment, the molar fraction of the AgI can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts or 0.6 parts.
[0038] In the present invention, the chemical composition of the red light perovskite quantum dot borosilicate glass material may include 56 to 68 parts of H3BO3, 28 to 34 parts of SiO2, 5 to 9 parts of ZnO, 13 to 17 parts of Na2CO3, 3 parts of Cs2CO3, 2 parts of PbBr2, 5 parts of PbI2, 1 part of NaBr, 3 parts of NaI and 0 to 0.6 parts of AgI, calculated by the amount of substances.
[0039] The present invention provides a method for preparing the red light perovskite quantum dot borosilicate glass material described in the above technical solution, comprising the following steps:
[0040] According to the chemical composition of the red light perovskite quantum dot borosilicate glass material, the prepared raw materials are mixed and then melted to obtain a glass melt;
[0041] The glass melt is cast and then cooled to obtain the red light perovskite quantum dot borosilicate glass material.
[0042] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0043] According to the chemical composition of the red light perovskite quantum dot borosilicate glass material, the present invention mixes the raw materials for preparation and then melts them to obtain a glass melt. In the present invention, the optional types and the amount of the raw materials for preparation can be the same as the types and the amount of the chemical composition of the prepared red light perovskite quantum dot borosilicate glass material, and will not be repeated here.
[0044] In the present invention, the melting temperature may be 1100-1250°C. In a specific embodiment, the melting temperature may be 1100°C, 1150°C, 1180°C, 1200°C or 1250°C. The melting time may be 10-20 minutes. In a specific embodiment, the melting time may be 10 minutes, 12 minutes, 15 minutes, 18 minutes or 20 minutes. In a specific embodiment, the mixing may include grinding and mixing. The present invention has no special restrictions on the grinding and mixing time and the particle size of the mixture obtained by grinding and mixing, as long as the prepared raw materials can be completely mixed. In a specific embodiment, the particle size of the mixture obtained by grinding and mixing may be 1-5 μm. In a specific embodiment, the particle size of the mixture obtained by grinding and mixing may be 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.
[0045] The present invention can place the mixed material obtained by mixing in a crucible, and place the crucible in a muffle furnace for melting. In a specific embodiment, the crucible can be an alumina crucible; and the muffle furnace can be a silicon carbide muffle furnace.
[0046] After obtaining the glass melt, the present invention casts the glass melt and then cools it to obtain the red light perovskite quantum dot borosilicate glass material.
[0047] In the present invention, the casting time may be less than 6 min. In a specific embodiment, the casting time may be 5.2 min, 5.3 min, 5.4 min, 5.5 min, 5.6 min, 5.7 min or 5.8 min.
[0048] In a specific embodiment, the casting molding may include: pouring the molten glass onto a preheated preheating plate and letting it stand. In the present invention, the temperature of the preheated preheating plate may be 300-450°C. In a specific embodiment, the temperature of the preheated preheating plate may be 300°C, 320°C, 350°C, 370°C, 400°C or 450°C; the casting time may be <1min. The present invention quickly (<1min) pours the molten glass onto a preheated preheating plate to prevent the molten glass from cooling and solidifying due to a slow casting speed and being unable to be poured out.
[0049] In a specific embodiment, the temperature of the standing still can be the same as the temperature of the preheating plate after preheating, which will not be described in detail here. In a specific embodiment, the standing still time can be 5 minutes. The present invention allows the preheating plate to stand still after pouring to prevent the glass melt from breaking due to a rapid drop in temperature.
[0050] In a specific embodiment, the cooling may include natural cooling; the final temperature of the cooling may be room temperature. The present invention uses a self-crystallization method, which does not require further annealing and heat treatment, is simple to operate, and reduces preparation energy consumption.
[0051] The present invention provides the application of the red light perovskite quantum dot borosilicate glass material described in the above technical solution or the red light perovskite quantum dot borosilicate glass material prepared by the preparation method described in the above technical solution in display, lighting or optical communication. The red light perovskite quantum dot borosilicate glass material provided by the present invention has high photoluminescence fluorescence quantum yield and good environmental stability. When applied to display, lighting or optical communication, it can maintain stability and high luminescence intensity in harsh environments.
[0052] In order to further illustrate the present invention, a red light perovskite quantum dot borosilicate glass material provided by the present invention and its preparation method and application are described in detail below in combination with embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0053] Example 1
[0054] Calculated by amount, 64 parts of H3BO3, 32 parts of SiO2, 7 parts of ZnO, 15 parts of Na2CO3, 3 parts of Cs2CO3, 2 parts of PbBr2, 5 parts of PbI2, 1 part of NaBr, 3 parts of NaI and 0.1 parts of AgI were ground and mixed to a particle size of about 2 μm, loaded into an alumina crucible, covered and placed in a muffle furnace, and melted at 1230°C for 15 minutes to obtain a glass melt.
[0055] The obtained glass melt was poured onto a preheating plate preheated to 400° C. within 1 minute, allowed to stand for 5 minutes, and then naturally cooled to room temperature to obtain a red light perovskite quantum dot borosilicate glass material (denoted as PG0.1).
[0056] Example 2
[0057] A red light perovskite quantum dot borosilicate glass material (denoted as PG0.2) was prepared according to the preparation method in Example 1. The only difference from Example 1 is that, in terms of the amount of substances, the preparation raw materials are: 64 parts of H3BO3, 32 parts of SiO2, 7 parts of ZnO, 15 parts of Na2CO3, 3 parts of Cs2CO3, 2 parts of PbBr2, 5 parts of PbI2, 1 part of NaBr, 3 parts of NaI and 0.2 parts of AgI.
[0058] Example 3
[0059] A red light perovskite quantum dot borosilicate glass material (denoted as PG0.4) was prepared according to the preparation method in Example 1. The only difference from Example 1 is that, in terms of the amount of substance, the preparation raw materials are: 64 parts of H3BO3, 32 parts of SiO2, 7 parts of ZnO, 15 parts of Na2CO3, 3 parts of Cs2CO3, 2 parts of PbBr2, 5 parts of PbI2, 1 part of NaBr, 3 parts of NaI and 0.4 parts of AgI.
[0060] Example 4
[0061] A red light perovskite quantum dot borosilicate glass material (denoted as PG0.6) was prepared according to the preparation method in Example 1. The only difference from Example 1 is that, in terms of the amount of substances, the preparation raw materials are: 64 parts of H3BO3, 32 parts of SiO2, 7 parts of ZnO, 15 parts of Na2CO3, 3 parts of Cs2CO3, 2 parts of PbBr2, 5 parts of PbI2, 1 part of NaBr, 3 parts of NaI and 0.6 parts of AgI.
[0062] Comparative Example 1
[0063] A red light perovskite quantum dot borosilicate glass material (denoted as PG) was prepared according to the preparation method in Example 1. The only difference from Example 1 is that, in terms of the amount of substances, the preparation raw materials are: 64 parts of H3BO3, 32 parts of SiO2, 7 parts of ZnO, 15 parts of Na2CO3, 3 parts of Cs2CO3, 2 parts of PbBr2, 5 parts of PbI2, 1 part of NaBr and 3 parts of NaI.
[0064] Figure 1 The XRD diffraction patterns of the red light perovskite quantum dot borosilicate glass materials prepared in Examples 1 to 4 and Comparative Example 1 are shown in FIG. Figure 1 It can be seen that when there is no AgI doping (Comparative Example 1), the XRD diffraction peak appears as a steamed bun peak of the glass, and with the increase in the amount of AgI substance, the XRD diffraction peak corresponding to the CsPbBrI2 perovskite quantum dots gradually increases, indicating that the doping of AgI is beneficial to promote the precipitation of CsPbBrI2 perovskite quantum dots in the red light perovskite quantum dot borosilicate glass material.
[0065] Figure 2 The emission spectra of the red light perovskite quantum dot borosilicate glass materials prepared in Examples 1 to 4 and Comparative Example 1 are shown in FIG. Figure 2It can be seen that AgI doping can significantly improve the photoluminescence intensity (PLQY) of CsPbBrI2 perovskite quantum dots. When the molar fraction of AgI is 0.4, the photoluminescence intensity of CsPbBrI2 perovskite quantum dots reaches the strongest. When the molar fraction of AgI is further increased to 0.6, the photoluminescence intensity of CsPbBrI2 perovskite quantum dots decreases, indicating that AgI doping can increase the crystallization rate of CsPbBrI2 perovskite quantum dots in red light perovskite quantum dot borosilicate glass materials, thereby increasing the luminescence intensity of CsPbBrI2 perovskite quantum dots. However, when the AgI doping concentration exceeds a certain value, too many CsPbBrI2 perovskite quantum dots are deposited in the glass, causing concentration quenching, resulting in a decrease in the luminescence intensity of CsPbBrI2 perovskite quantum dot glass. However, compared with the undoped sample PG, the photoluminescence intensity of PG0.6 is still higher.
[0066] Figure 3 PLQY diagram of the red light perovskite quantum dot borosilicate glass material prepared in Comparative Example 1. Figure 3 It can be seen that the PLQY of the red light perovskite quantum dot borosilicate glass material prepared in Comparative Example 1 is 20.3%.
[0067] Figure 4 PLQY diagram of the red light perovskite quantum dot borosilicate glass material prepared in Example 3. Figure 4 It can be seen that the red light perovskite quantum dot borosilicate glass material prepared in Example 3 is doped with 0.4 parts of AgI in terms of the amount of substance, and its PLQY is increased to 62.4%.
[0068] Figure 5 The lifetime decay curve of the red light perovskite quantum dot borosilicate glass material prepared in Examples 1 to 4 and Comparative Example 1 is shown in FIG. Figure 5 It can be seen that the lifetime values of the red light perovskite quantum dot borosilicate glass materials obtained in Comparative Example 1, Example 1, Example 2, Example 3 and Example 4 are 213ns (nanoseconds), 245ns, 253ns, 306ns and 288ns, respectively, indicating that in addition to increasing the crystallization rate of CsPbBrI2 perovskite quantum dots in glass, AgI doping can also reduce the surface defects of CsPbBrI2 perovskite quantum dots to a certain extent, thereby improving its photoluminescence intensity.
[0069] Figure 6 This is a graph showing the change in photoluminescence intensity of the red light perovskite quantum dot borosilicate glass material prepared in Example 3 after being immersed in water for 90 days, wherein the inner lining graphs are, from left to right and from top to bottom, photos of PG0.4 under a 365nm ultraviolet lamp after 0 days, 10 days, 20 days, 30 days, 40 days, 50 days, 60 days, 70 days, 80 days and 90 days. Figure 6 It can be seen that after 90 days of immersion in water, PG0.4 still has bright luminescence, and its photoluminescence intensity is 88.9% of the original value, indicating that the prepared red light perovskite quantum dot borosilicate glass material has good water stability.
[0070] Figure 7 This is a graph showing the change in photoluminescence intensity of the red light perovskite quantum dot borosilicate glass material obtained in Example 3 after continuous irradiation with 6W ultraviolet light for 90 days, wherein the inner lining graphs are, from left to right and from top to bottom, photos of PG0.4 under 365nm ultraviolet light after 0 days, 10 days, 20 days, 30 days, 40 days, 50 days, 60 days, 70 days, 80 days and 90 days. Figure 7 It can be seen that after 90 days of ultraviolet light irradiation, PG0.4 still has bright luminescence, and its photoluminescence intensity is 90% of the original value, indicating that the prepared red light perovskite quantum dot borosilicate glass material has good photostability.
[0071] Figure 8 The photoluminescence intensity variation diagram of the red light perovskite quantum dot borosilicate glass material prepared in Example 3 after five cycles at 300K and 400K. Figure 8 It can be seen that after 5 hot and cold cycles, PG0.4 still has a luminescence intensity of 98% of the original value at room temperature, indicating that the prepared red light perovskite quantum dot borosilicate glass material has good thermal stability.
[0072] In summary, the present invention can prepare red-light perovskite quantum dot borosilicate glass material with high luminescence intensity in borate glass through AgI doping and self-crystallization. Moreover, the red-light perovskite quantum dot borosilicate glass material provided by the present invention has excellent water stability, light stability and thermal stability, and excellent environmental stability.
[0073] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A red light perovskite quantum dot borosilicate glass material, the chemical composition of which, in terms of the amount of substance, comprises: H3BO3 56-68 parts, SiO2 28-34 parts, ZnO 5-9 parts, Na2CO3 13-17 parts, Cs2CO3 1-5 parts, PbBr2 1-4 parts, PbI2 3-7 parts, NaBr 1-2 parts, NaI 1-4 parts and AgI 0-0.6 parts, and the amount of AgI is not 0.
2. The red light perovskite quantum dot borosilicate glass material according to claim 1, characterized in that: Calculated by amount of substance, the chemical composition of the red light perovskite quantum dot borosilicate glass material includes 56 to 68 parts of H3BO3, 28 to 34 parts of SiO2, 5 to 9 parts of ZnO, 13 to 17 parts of Na2CO3, 3 parts of Cs2CO3, 2 parts of PbBr2, 5 parts of PbI2, 1 part of NaBr, 3 parts of NaI and 0 to 0.6 parts of AgI.
3. The method for preparing the red light perovskite quantum dot borosilicate glass material according to any one of claims 1 to 2, characterized in that: The following steps are involved: According to the chemical composition of the red light perovskite quantum dot borosilicate glass material, the prepared raw materials are mixed and then melted to obtain a glass melt; The glass melt is cast and then cooled to obtain the red light perovskite quantum dot borosilicate glass material.
4. The preparation method according to claim 3, characterized in that: The melting temperature is 1100-1250° C. and the melting time is 10-20 minutes.
5. The preparation method according to claim 3, characterized in that: The mixing includes grinding and mixing; the particle size of the mixture obtained by grinding and mixing is 1 to 5 μm.
6. The preparation method according to claim 3, characterized in that: The pouring molding time is less than 6 minutes.
7. The preparation method according to claim 3 or 6, characterized in that: The casting molding comprises: pouring the glass melt onto a preheated plate and letting it stand.
8. The preparation method according to claim 7, characterized in that: The temperature of the preheated preheating plate is 300-450°C.
9. The preparation method according to claim 7, characterized in that: The pouring time is less than 1 min.
10. Use of the red light perovskite quantum dot borosilicate glass material according to any one of claims 1 to 2 or the red light perovskite quantum dot borosilicate glass material prepared by the preparation method according to any one of claims 3 to 9 in display, lighting or optical communication.
Citation Information
Patent Citations
Silver iodide quantum dot-perovskite blended layer, in-situ preparation method and solar battery without hole transmission layer
CN106848061A
Method for preparing halogen perovskite quantum dot glass from heavy metal waste residues and halogen-containing wastewater
CN111153595A
Inorganic perovskite quantum dot glass and preparation method thereof
CN115849721A
Method for enhancing luminescence of perovskite quantum dot glass
CN117142763A
Method for improving luminescent property of perovskite quantum dot glass and application thereof
CN118324409A
